2023
DOI: 10.3390/ijms24021694
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Menthol Impairs Mucociliary Clearance via TRPM8 and MUC5AC/MUC5B in Primary Airway Epithelial Cells

Abstract: Flavorings enhance the palatability of e-cigarettes (e-cigs), with menthol remaining a popular choice among e-cig users. Menthol flavor remains one of the only flavors approved by the United States FDA for use in commercially available, pod-based e-cigs. However, the safety of inhaled menthol at the high concentrations used in e-cigs remains unclear. Here, we tested the effects of menthol on parameters of mucociliary clearance (MCC) in air–liquid interface (ALI) cultures of primary airway epithelial cells. ALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The functional significance of this finding is unknown. There is evidence that menthol 51 and nicotine 52 may alter airway mucus properties. JMi aerosol had higher nicotine concentrations than air controls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of this finding is unknown. There is evidence that menthol 51 and nicotine 52 may alter airway mucus properties. JMi aerosol had higher nicotine concentrations than air controls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, smokers are more likely to hold the smoke and breath deeper [ 46 ], which in theory would lead to a higher particle deposition [ 47 ]. Additionally, study has reported a reduction in ciliary beating frequency following exposure to menthol-containing tobacco products, which impairs mucociliary clearance of deposited particle in airway [ 48 , 49 ]. Based on this, we had hypothesized that the overall deposition fraction would be higher with mentholated little cigars than the regular little cigars.…”
Section: Discussionmentioning
confidence: 99%